The nurse and family helath strategy: contribution for assistencial model change - Roberta Kaliny de Souza Costa; Francisco Arnoldo Nunes de Miranda (Rev Rene)
The present study makes a brief reflection regarding the nursing action in Family Health Strategy – ESF, identifying its contributions in the construction of basic attention to health and in assistance model change, in the perspective of the Public Health System – SUS. It’s elicited the enlargement of insertion and nurse relevance in the ESF, having in mind the experience acquired by this professional in planning, execution and evaluation of assistance, managing and educational actions, which is fundamental for the development of the strategy. It’s concluded that in spite of assuming a fundamental role on ESF and contributing with rearrangement proposals to services in SUS logistics, the nurse still needs to be prepared to guarantee integrality, quality and humanization of attendance, in defense of a sanitary project which is dreamt do be built in the health area.